Comparative study between cervical polyetheretherketone cages and dynamic cervical implant postanterior cervical discectomy - Mostafa G Eldin; Mohammed S Mohammed (Wolters Kluwer Medknow Publications, 2018)
Objective This is a prospective comparative study between polyetheretherketone (PEEK) cages and dynamic cervical implants (DCI) to evaluate the safety, the effectiveness, and the clinical outcome with radiological outcome for patients with single-level degenerated cervical disc disease treated by anterior cervical discectomy. Patients and methods We studied 30 patients with single-level cervical disc disease. Preoperative evaluation included plain cervical radiography including dynamic views. MRI was carried out to confirm the clinical diagnosis. Results Our study showed that the procedures of two groups were safe and easy without major complications and do not show significant differences between DCI and anterior cervical discectomy and fusion (ACDF) with PEEK cages in terms of improvement in clinical symptoms, blood loss, or operation time; however, DCI was associated with better postoperative neck disability index scores and also resulted in better overall cervical range of motion and segmental range of motion at the treated level than ACDF with PEEK cage. ACDF with PEEK cage is still the gold standard technique for treatment of cervical degenerative disc disease. It improves patient activity and provides a stable segment. However, it fails to restore normal cervical biomechanics and does not prevent adjacent segment disease. Conclusion DCI is considered as a new strategy and an intermediate stage between ACDF and total disc replacement.